P–472 Single mothers by choice - experiences of single women seeking treatment at a public fertility clinic in Denmark: A pilot study. (6th August 2021) - Steenberg, M L; Sylvest, R; Koert, E; Schmidt, L
Abstract: Study question: Are single women in fertility treatment stigmatised and what do they experience? Summary answer: The women did not feel stigmatised. They experienced self-blame and negative thoughts about themselves, despite experiencing empowerment and receiving positive reactions from families and friends. What is known already: Since 2007, medical doctors in Denmark have been permitted to offer medically assisted reproduction (MAR) also to single women. Denmark is a welfare state with a public health care sector providing MAR free of charge, 240 days of paid parental leave, and public full-time day-care. There has been an increase in the number of single women deciding to have children through the use of MAR. These women are referred to as 'single mothers by choice' (SMC), and they have been criticised for being selfish when raising a child without a father. Previous studies have shown how SMC can feel stigmatised. Study design, size, duration: Semi-structured qualitative interviews at a public fertility clinic in Copenhagen, Denmark. Data collection took place between September and October 2020. Participants/materials, setting, methods: The participants were single and childless women (N = 6) undergoing MAR at the Fertility Clinic, Rigshospitalet in Copenhagen, Denmark. Five women received IVF and one received IUI. The women were between 30 and 40 years old and were all residents in the Capital Region of Denmark. The interviews were audiotaped, anonymised, and transcribed in full. Data were analysed using qualitative content analysis. Main results and the role of chance: Single women did not differ from cohabiting women seeking MAR in relation to their experiences and attitudes towards motherhood. Four main themes were identified; (1) Experiences of single women seeking fertility treatment, (2) Emotions associated with becoming a single mother by choice, (3) The decision of becoming a single mother by choice, and (4) Family formation – a social interaction. The women would have preferred to have a child in a relationship with a partner and the shattered dream about the nuclear family has caused a wide range of experiences and emotions. The women did not feel stigmatised but they all had an awareness of the prejudices other people might have towards single mothers by choice. Hence, they were ready to defend their choice if necessary. On the other hand, they had received positive reactions and the process of becoming a single mother by choice was influenced by their social relations with family and friends. Despite their dream of the nuclear family the women choose to become SMC because motherhood was of such importance and they feared they would otherwise become too old to have children – the biological clock was ticking. Limitations, reasons for caution: The participants were recruited from a public fertility clinic in the Capital Region of Denmark and may not be representative of all single women seeking MAR. Results might not be transferable to other countries with a different cultural context regarding the societal acceptance of different ways to establish a family. Wider implications of the findings: This study contributes to the understanding of the experiences of single women seeking fertility treatment in a welfare state where there are no differences in the possibilities for different social classes to seek MAR in the public health care sector. Trial registration number: N/A